2022
DOI: 10.1016/j.mnl.2021.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Where Do We Go From Here?

Abstract: The COVID-19 pandemic has impacted nurses transitioning to practice in a variety of ways over the past two years. Analysis from the Versant Database comparing new graduate nurses (NGNs) from 2018-2021 revealed a widened practice gap for NGNs in these specialty areas of practice: critical care, perinatal, and emergency. Additionally, NGNs achieved 100% competency validation sooner in 2020/2021. The analysis also revealed greater diversity of NGNs who participated in a transition to practice (TTP) program in 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In the transition from student to professional nurse, Masso et al (2022) asserted that there is a need to shift the focus from whether an NLN is ready for the workplace to the workplace being ready to support NLNs. Retention of NLNs entering the profession is imperative, as estimates demonstrate a first-year turnover of 25.3%, with replacement costs ranging between $10,098 and $88,000 per nurse (Grubaugh et al, 2022). Then, with the stress and burnout faced by bedside nurses during the pandemic, unprecedented numbers of experienced nurses are retiring or leaving the bedside for lucrative positions as travel nurses (Yang & Mason, 2022), further impacting retention rates.…”
Section: Discussionmentioning
confidence: 99%
“…In the transition from student to professional nurse, Masso et al (2022) asserted that there is a need to shift the focus from whether an NLN is ready for the workplace to the workplace being ready to support NLNs. Retention of NLNs entering the profession is imperative, as estimates demonstrate a first-year turnover of 25.3%, with replacement costs ranging between $10,098 and $88,000 per nurse (Grubaugh et al, 2022). Then, with the stress and burnout faced by bedside nurses during the pandemic, unprecedented numbers of experienced nurses are retiring or leaving the bedside for lucrative positions as travel nurses (Yang & Mason, 2022), further impacting retention rates.…”
Section: Discussionmentioning
confidence: 99%
“…Historically nurse transition is described as stressful and shocking 16. Transition experiences worsened because alternative teaching and learning methods widened existing academic-practice gaps 2. Decreased readiness for practice was evident from a lack of soft skills such as interprofessional communication, the inability to manage full patient-care assignments or recognize patient deterioration, and insufficient skill mastery 6,7,17-21.…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…Organizational factors, such as increased workload, unfamiliar procedures, patient acuity, frequent policy changes, and rapid patient and staff turnover further influenced NGN transition experiences 2,6,24. Compounded by unsupportive peers and leaders, these challenges exacerbated anxiety, role stress, moral distress, and disillusionment with nursing 6,14,16,20.…”
Section: Background/literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…When asked about their biggest fears, NGNs stated that being overwhelmed, being unsafe by omission or commission, and ensuring that they are performing the responsibilities of a professional nurse are their top 3 concerns 11. A greater practice gap was identified among NGNs who completed a TTP program in 2020-2021 as compared with 2018-2019, specifically NGNs who were hired into perinatal, emergency, and critical care, resulting in the need for hiring organizations to provide additional remediation prior to assessment and validation of clinical performance 15. A study conducted by Bultas and L'Ecuyer16 found that a large number of NGNs have a negative perception of their TTP at 6 months and up to 12 months, recommending additional touch points to assess skills, competency, manage stress, and learn self-care strategies.…”
Section: Introductionmentioning
confidence: 99%